Effect of Ghrelin Antagonist on Serum Testosterone and Luteinizing Hormone in Obese Type 2 Diabetic Mice - Lubna Siddique , Umbreen Ahmed , Tausif Ahmed Rajput, (Journal of Rawalpindi Medical College, 2014)
Background: To determine the effect of ghrelin antagonist (D-Lys3) on plasma glucose, insulin resistance, serum testosterone and luteinizing hormone levels, on obese and type 2 diabetic mice. Methods: Fifty healthy BALB/c mice were divided into five groups. Mice in group II to V were fed high-fat diet for 4 weeks followed by intraperitoneal (IP) injection of streptozotocin to group IV and V to induce type 2 diabetes mellitus. Group I served as control.Groups II and III were obese and group IV and V were diabetic. Groups III and V were injected ghrelin antagonist IP for 6 days. Terminal intracardiac blood extraction was done and samples were analyzed for fasting plasma glucose, serum insulin, testosterone and luteinizing hormone. Insulin resistance was calculated by homeostatic model assessment for insulin resistance. Results: Plasma glucose level and insulin resistance decreased and serum testosterone and luteinizing hormone levels increased after using ghrelin antagonist in group III and V. Conclusion: Glucose level and insulin resistance were significantly decreased in obese and type 2 diabetic mice after ghrelin antagonist administration. Whereas serum testosterone and luteinizing hormone levels were increased